2011
DOI: 10.15603/2176-1019/mud.v19n1-2p79-88
|View full text |Cite
|
Sign up to set email alerts
|

Percepção do Paciente Portador de Esclerose Múltipla Sobre o Diagnóstico e Tratamento

Abstract: ResumoO objetivo do presente artigo foi identificar o comportamento do paciente portador de esclerose múltipla após o recebimento do diagnóstico, com base em entrevista semiestruturada. A pesquisa foi realizada com estudo do discurso dez pacientes, buscando investigar as principais características presentes. Os relatos estudados indicam que os pacientes em geral têm dificuldades para aceitação do diagnóstico, devido à falta de informação sobre a origem da patologia e as características dos sintomas apresentado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies indicate that the development or aggravation of depression in people with MS is related to the impairment of physical abilities, since this impairment causes increased dependence to perform basic activities and causes patients to need more support from relatives and caregivers, often causing anxiety and emotional stress 22 . In this context, the results of this study showed that depression is directly related to the impairment of physical capacities and the emotional aspect of patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the development or aggravation of depression in people with MS is related to the impairment of physical abilities, since this impairment causes increased dependence to perform basic activities and causes patients to need more support from relatives and caregivers, often causing anxiety and emotional stress 22 . In this context, the results of this study showed that depression is directly related to the impairment of physical capacities and the emotional aspect of patients with MS.…”
Section: Discussionmentioning
confidence: 99%